THYROID FUNCTIONS IN PREGNANT WOMEN WITH GESTATIONAL HYPERTENSION - Sattar, Rabia; Cheema, Abdul Majeed (Pakistan Journal of Physiology, 2017)
Background: In normal pregnancy, changes in thyroid function are well acknowledged; however, information about thyroid function in gestational hypertension (GH) is scanty. Hypertensive disorders complicating pregnancy are common and contribute greatly to prenatal and maternal morbidity and mortality in the developing countries. The aim of this study was to investigate thyroid functions in pregnant women with gestational hypertension. Methods: This was a case-control study evaluated maternal thyroid hormonal status in 78 (62 hypertensive and 16 normotensive) women with pregnancy of >20 weeks to term, referred to Jinnah Hospital, Lahore. Thyrotropin (TSH), Total thyroxine (tT4) and Total triiodothyronine (tT3) were assayed with ELISA. Results: Serum TSH and tT3 were significantly higher in hypertensive pregnant (HP) compared to normotensive pregnant women (p=0.002, p=0.039 respectively). Mean serum TSH was 3.28±0.29 µIU/ml in normotensive pregnant subjects and 6.71±1.06 µIU/ml in HP subjects, whereas mean serum tT3 in normotensive subjects was 1.22±0.03 ηg/ml and 1.31±0.21 ηg/ml in the HP subjects. There were no significant differences in serum tT4 levels of the subjects. Conclusion: Mean serum TSH and tT3 levels were significantly increased without concomitant changes in tT4 in HP compared to normal pregnant women. Raised TSH and tT3 levels might be associated with a risk for occurrence of gestational hypertension. Pak J Physiol 2017;13(1):30–2